Isotope Shifts in High Lying Levels of Dy I and Er I by High-Resolution UV Laser Spectroscopy. (29th November 2011) - Jin, Wei-Guo; Ono, Hiroaki; Minowa, Tatsuya
Abstract : High-resolution atomic-beam ultraviolet (UV) laser spectroscopy in Dy I and Er I has been performed. Isotope shifts have been measured for two transitions in Dy I and one transition in Er I. Specific mass shifts and field shifts have been derived for the studied transitions, and large differences between the two4 f 10 6 s 2 –4 f 10 6 s 6 p transitions in Dy I have been found. From the derived specific mass shifts and field shifts, configuration mixing at the upper levels of transitions has been discussed.